FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN KELUARGA DALAM MEMBERIKAN PERAWATAN KEPADA PASIEN STROKE PASCA HOSPITALISASI - Lalu M. Panji Azali; Ririn Afrian Sulistyawati; Galih Setia Adi (Universitas Kusuma Husada Surakarta, 2021)
Stroke is a disease that is categorizes as a cause of disability and requires a long treatment for many sufferers, so that what we're needed and complex is to meet the needs of rehabilitation for patients. The family is the main source of informal support that plays an important role in providing long-term care assistance to dependent stroke patients, both in the form of functional, social and knowledge assistance in fulfilling the Activity of Daily Living (ADL), so it is important for families to have knowledge of stroke patient care. the good one. This study aims to determine the factors related to the knowledge of post-hospitalization stroke patients, including age, education, occupation, gender, nursing experience and sources of information. questionnaire, the number of samples as many as 30 respondents. The data analysis used was the bivariate person test, the Independent t test, the Kruskal Walllist test as a candidate test and the multivariate multiple linear regression test to assess the influenced of the dominant factor. Based on the data analysis, the results obtained that the variables that meet the requirements to continue to do multivariate analysis Linear regression test are education variables with a p value of 0.008, age with a p value of 0.19 and sources of information with a p value of 0.016 (p value < 0, 25). Based on the multivariate data analysis, the linear regression test showed that the education variable has a dominated influence on knowledge with a p value of 0.04 (p value <0.05), with a linear regression equation y = 0.646-0.109 and a coefficient determination (R2 ) 0.350 which means that the education variable contributes to influence knowledge by 35.0% while 65.0% is influenced by other factors. The conclusion in this study is that the education variable is the most dominant variable influencing family knowledge in providing care to stroke patients after hospitalization.